2021
DOI: 10.1371/journal.pone.0246324
|View full text |Cite
|
Sign up to set email alerts
|

Improving the prioritization of children at the emergency department: Updating the Manchester Triage System using vital signs

Abstract: Background Vital signs are used in emergency care settings in the first assessment of children to identify those that need immediate attention. We aimed to develop and validate vital sign based Manchester Triage System (MTS) discriminators to improve triage of children at the emergency department. Methods and findings The TrIAGE project is a prospective observational study based on electronic health record data from five European EDs (Netherlands (n = 2), United Kingdom, Austria, and Portugal). In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Many triage nurses in China evaluate patient conditions based on their own intuition and experience, not a standardized objective indicators. Vital signs have been proved to be an important part in triage assessment [ 18 ] and an important predictor of disease progression [ 19 ]. The results of Zachariasse et al [ 18 ] have shown that the determining cut-off values of vital signs for patients of different age groups can help nurses triage the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many triage nurses in China evaluate patient conditions based on their own intuition and experience, not a standardized objective indicators. Vital signs have been proved to be an important part in triage assessment [ 18 ] and an important predictor of disease progression [ 19 ]. The results of Zachariasse et al [ 18 ] have shown that the determining cut-off values of vital signs for patients of different age groups can help nurses triage the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vital signs have been proved to be an important part in triage assessment [ 18 ] and an important predictor of disease progression [ 19 ]. The results of Zachariasse et al [ 18 ] have shown that the determining cut-off values of vital signs for patients of different age groups can help nurses triage the patients. However, Zachariasse et al did not elaborate on age group classification.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical relevance and given the low numbers in the ’immediate group’ and non-urgent category, we combined immediate/very urgent and standard/non-urgent, resulting in a three-level triage urgency variable. Severity of an ED visit was determined based on type of management during the entire ED visit similar to the approach in the TrIAGE project [ 18 , 19 ] ( S1 Table ), and included the levels not severe, severe and very severe.…”
Section: Methodsmentioning
confidence: 99%
“…10,38 Lack of an international EWS is likely related to the view that an EWS in one hospital may not be applicable in another owing to different patient characteristics, which suggests one single EWS may not meet the needs of unique patient populations. 40,42 This is reflected in hospitals that have developed their own EWS, such as a paediatric EWS, 43 or a modified EWS. 44…”
Section: Early Warning Scoring Systemmentioning
confidence: 99%